Evaluation of the Synergistic Antimicrobial Activity of Essential Oils and Cecropin A Natural Peptide on Gram-Negative Bacteria - Filippo Fratini; Chiara Pecorini; Ilaria Resci; Emma Copelotti; Francesca Paola Nocera; Basma Najar; Simone Mancini (Animals)
In an era dominated by the phenomenon of antibiotic resistance, it is increasingly important to look for alternatives to synthetic antibiotics. In light of these considerations, the synergistic use of essential oils and Antimicrobial Peptides (AMPs) seems a viable strategy. In this study, we assessed the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Fractional Inhibitory Concentration (FIC) of three Essential Oils (EOs): winter savory (Satureja montana), bergamot (Citrus bergamia) and cinnamon (Cinnamomum zeylanicum) and of the insect antimicrobial peptide Cecropin A (CecA), alone and in combination with EOs, against two Gram-negative ATCC bacterial strains: Escherichia coli and Salmonella enterica serovar Typhimurium. The MIC results showed that winter savory EO (SmEO) and cinnamon EO (CzEO) exhibited the strongest antibacterial activity against both bacterial strains, whereas bergamot EO (CbEO) and CecA demonstrated comparatively lower antibacterial efficacy. These results were also confirmed by the MBC values. The FIC Indices (FICI) revealed that the most effective synergies were observed with the combinations SmEO/CzEO and SmEO/CbEO against E. coli, while against S. enterica Typhimurium the best combinations were CbEO/CzEO and SmEO/CzEO. Regarding CecA, although it was not the most efficient agent either individually or in combination, it is noteworthy that, when combined, it exhibited antibacterial activity even at a 1:64 dilution.